Prevalence and effect of schistosome and soil-transmitted helminth infection on labour input in rice-growing communities of Ogun State, Nigeria - Sammy Olufemi Sam-Wobo; Olushola Akintola; Jonathan Atungwu; Uwem Friday Ekpo; Monsuru Alani Adeleke; Chiedu Felix Mafiana (Epidemiology, Biostatistics and Public Health)
Schistosomiasis and soil-transmitted helminthiasis (STH) are public health problems in communities which lack basic social amenities with poor hygienic conditions. Studies were carried out to determine the prevalence and effect of schistosomes and soil-transmitted helminths infection on labour input on rice production in 9 rice-growing communities of Ogun State. Parasitological examinations of urine and faecal samples, and structured questionnaires were conducted on 243 consented individuals from May 2009 to March 2010. The results showed an overall prevalence of 17% for Ascaris lumbricoides, 12% for hookworms, 2% for Trichuris trichiura, 1% for Schistosoma haematobium and 1% for Schistosoma mansoni. A. lumbricoides and hookworms were more prevalent in Agbajege (25%), and varied in the other 8 communities. T. trichiura was prevalent in three communities, Agbajege (5%), Akodu (4.2%), and Moloko-Asipa (4.8 %); S. haematobium was prevalent only in Ayedere (2.6%) and Lufoko (8%), while S. mansoni was prevalent only in Moloko-Asipa (9.5%). Infections among the gender were varied as 26.3 % of males and 33.8 % of females had an overall prevalence of: A. lumbricoides (16.8%), hookworms (11.8%), T. trichiura (1.6%), S. haematobium (1.1%) and S. mansoni (1.1%). On frequency of infection to incapacitation per year, 45% of respondents were incapacitated 1-2 times, 27% 3-4 times and 19% were incapacitated more than 4 times. Understanding the effect of these two diseases will not only improve the health status of residents but also increase their productivity and ensure food security.